Pyogenic Liver Abscess: Contemporary Trends in a Tertiary Institute - Elad Boaz; Eli Ben-Chetrit; Yonathan Bokhobza; Shlomo Yellinek; Menahem Ben-Haim; Petachia Reissman; Amir Dagan (International Journal of Clinical Practice)
Background. Pyogenic liver abscess (PLA) is an uncommon but potentially life-threatening condition. In recent years, advances in diagnostics and management have led to early diagnosis and treatment and decreased mortality. We present recent data from a large series of patients with PLA and examine the trends in the management of PLA over a period of 50 years. Methods. The medical records of all patients admitted to the Shaare Zedek Medical Center, Israel, between January 2011 and December 2021 with a primary or secondary diagnosis of PLA were reviewed retrospectively. Results: Ninety-five patients with PLA were identified. Thirty-eight (40%) were female. The median patient age was 66 years (range 18–93). The diagnosis of PLA in all patients was confirmed with abdominal computed tomography (CT). In twenty patients (21.1%), PLA was not diagnosed by the initial abdominal US. Most abscesses were right-sided. Biliary tract origin was the most common underlying cause of PLA (n = 57, 60%), followed by cryptogenic etiology (n = 28, 30%). Escherichia coli, Klebsiella pneumoniae, and Streptococcus species were most commonly identified. The most common primary treatment modality was percutaneous drainage (PD), which was performed in 81 patients (85.3%). Fourteen patients (14.7%) were treated medically without intervention, and two patients (2.1%) were treated surgically following a failure of PD. Four patients died as a direct result of PLA. Conclusions. Patients diagnosed with PLA are older, the male predominance is less pronounced, and the offending pathogens are likely to originate from the biliary tract. This study questions the utility of abdominal US as the initial diagnostic imaging in patients with suspected PLA (versus CT) and demonstrates improved outcomes for patients with PLA over the years.